Women or gender, anti-poverty or empowerment? : misplaced polarities in state-led poverty programming in the Caribbean (2001)
Argues that the current policy fashion, to target or not to target women for anti-poverty resources is premised on misplaced polarities. Notes that it does not take into account institutional constraints that prevent outcomes for male-relevant strategies from materialising in identical ways for women.
Keywords: POVERTY ALLEVIATION